Analysis of Physical and Mental Workload on Emergency Department (ED) Nurses with Subjective Workload Assessment Technique (SWAT) and Cardiovascular Load (CVL) Methods (Case Study of Sidoarjo City Hospital) - Raden Bramantia Rukmana; Rusindiyanto Rusindiyanto (Universitas Batanghari Jambi, 2023)
This research was conducted to reveal the amount of mental and physical workloads of nurses, determine the SWAT and CVL indicators which contribute the most impact on the occurrence of workloads, and advise on possible improvements to minimize this workload. The study was carried out in the Emergency Department of RSUD Sidoarjo from May 2023 until the required data is complete. The result of this analysis revealed that the most impactful SWAT indicator on nurses' mental workloads is Time, Shift 1 62.34%, Shift 2 59.13%, and Shift 3 57.19%. Meanwhile, the result of the examination on physical workload using the CVL method with a percentage of 30% states that the highest CVL average percentage is 33%. Based on the results of both indicators, Sidoarjo Regional Hospital is advised to add one more nurse so that the workload of nurses overall can be reduced.